ANALYSIS OF THE INFLUENCE OF NIM, NPL, AND BOPO ON ROA OF FINANCING COMPANIES FOR THE PERIOD 2021–2024 - Oktono, Ricky; Tampubolon, Lambok DR (Journal of Social and Economics Research, 2025)
This study aims to analyze the impact of Net Interest Margin (NIM), Non‑Performing Loan (NPL), and the Operational Expense to Operational Income Ratio (BOPO) on Return on Assets (ROA) in financing companies in Indonesia. This study employs a quantitative approach using secondary data sourced from 11 financing companies listed on the Indonesia Stock Exchange (IDX). The analysis is conducted using multiple regression methods, including descriptive statistical tests, classical assumption tests, coefficient of determination calculations, and hypothesis testing to evaluate the influence of NIM, NPL, and BOPO on ROA. The analysis results show that Net Interest Margin (NIM), Non‑Performing Loan (NPL), and the Operational Expense to Operational Income Ratio (BOPO) have a significant impact, both partially and collectively, on Return on Assets (ROA). The coefficient of determination (R‑Square) value of 81.2% indicates that these three variables provide a strong contribution in explaining the variation in ROA among financing companies in Indonesia.